A new Cephalobium Cobb (Nematoda, Cephalobiidae), a parasite of Anurogryllus Muticus (De Geer) (Orthoptera, Gryllidae) from Argentina - Camino, Nora B.; Brividoro, Melina; Leyh, Gabriela (Papéis Avulsos de Zoologia, 2006)
A new species of Cephalobium from Gorina, La Plata, Argentina, parasiting nymphs of Anurogryllus muticus (De Geer) (Orthoptera, Gryllidae) is described and illustrated. This nematode can be characterized by having the stoma longer than broad, the glottoid apparatus anisoglottid and anisomorphic, divided into two portions, one with cuticularized walls and the other with three simple dorsal teeth. The male is further characterized by the presence of two long and separated spicules and short gubernaculum without any projection. Genital papillae are arranged in five postanal pairs.